Handbook of adhesives and sealants. Volume 2, general knowledge, application techniques, new curing techniques - Cognard, Philippe (Elsevier, 2006)
Contributions from more than 60 authors, each a well-known specialist in their field, have been co-ordinated to produce the most comprehensive Handbook of Adhesives and Sealants ever published. The handbook will be published as 8 volumes, over a period of 4 years and will contain over 2800 pages, rich with case studies, industrial applications and the latest research. It is a work in progress, enabling the latest new and important applications to be included as they happen. Volume 2 of Elseviers Handbook of Adhesives & Sealants Series, General knowledge, application of adhesives & new curing techniques, covers the mechanisms of adhesion, its application, and drying and curing techniques. The volume is divided in to the following sections: Theory of adhesion Metering and dispensing Design and calculation of bonded joints Heat stable adhesives UV curing Flexible bonding and sealants Each contributing author is a scientist, practitioner, engineer, or chemist with an abundance of practical experience in their respective field, making this text an authoritative reference source for any materials scientist or engineer, whether in academia or industry.
Keywords: Adhesives.; Adhesives -- Industrial applications.; Sealing compounds.; Sealing compounds -- Industrial applications.; elektronické knihy; electronic books